#### Answer

$-\dfrac {3}{2}$

#### Work Step by Step

$e^{3-x}=\left( e^{3}\right) ^{-x}\Rightarrow e^{3-x}=e^{-3x}\Rightarrow 3-x=-3x\Rightarrow 2x=-3\Rightarrow x=-\dfrac {3}{2}$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$-\dfrac {3}{2}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.